Analisis Yuridis Pengembalian Barang Bukti Dalam Tindak Pidana Perikanan (Juridical Analysis Of Returns Of Investigation Goods Action Of Fisheries Criminal) - Ibrahim Nainggolan (Universitas Muhammadiyah Sumatera Utara, 2018)
Fisheries in Indonesia is one of the natural resources which is a gift from God the Almighty that must be managed in such a way that can improve people's welfare in accordance with the provisions of the 1945 Constitution Article 33 paragraph (3) stated,